2005
DOI: 10.1038/sj.npp.1300819
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for the Preferential Involvement of 5-HT2A Serotonin Receptors in Stress- and Drug-Induced Dopamine Release in the Rat Medial Prefrontal Cortex

Abstract: The mechanism(s) by which serotonin modulates dopamine release in the medial prefrontal cortex is not known, although studies suggest an involvement of 5-HT2 family receptors. We employed in vivo microdialysis and putatively selective 5-HT2A antagonists (M100907, MDL 11,939, SR46349B) to determine if 5-HT2A receptors are responsible for both drug-and stress-induced DA release in the medial prefrontal cortex. MDL 11,939 and SR46349B receptor-binding studies indicated, for the first time, that only MDL 11,939 ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
107
0
3

Year Published

2006
2006
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 174 publications
(117 citation statements)
references
References 77 publications
7
107
0
3
Order By: Relevance
“…Thus, 5-HT2A receptor agonism may increase the activity of corticotegmental glutamatergic projection neurons. This suggestion is supported by our recent finding that systemic administration of the 5-HT2 receptor agonist DOI increased glutamate efflux in the VTA (Pehek et al, 2006). Infusions of M100907, directly into the PFC, blocked this increase, implying that the relevant 5HT2A receptors were localized in the PFC (Pehek et al, 2006).…”
Section: Mesocortical Pathwaysupporting
confidence: 64%
See 2 more Smart Citations
“…Thus, 5-HT2A receptor agonism may increase the activity of corticotegmental glutamatergic projection neurons. This suggestion is supported by our recent finding that systemic administration of the 5-HT2 receptor agonist DOI increased glutamate efflux in the VTA (Pehek et al, 2006). Infusions of M100907, directly into the PFC, blocked this increase, implying that the relevant 5HT2A receptors were localized in the PFC (Pehek et al, 2006).…”
Section: Mesocortical Pathwaysupporting
confidence: 64%
“…We have demonstrated that intracortical infusions of the 5-HT2A receptor antagonists M100907 or MDL 11,939 blocked the increases in cortical DA produced by the systemic administration of the 5-HT2 receptor agonist DOI (Pehek et al, 2001;Pehek et al, 2006). Furthermore, infusions of M100907 blocked physiologically-induced DA release in the PFC, namely that produced by a mild stressor (gentle handling; Pehek et al, 2006).…”
Section: Mesocortical Pathwaymentioning
confidence: 96%
See 1 more Smart Citation
“…In humans, one study suggested that during amphetamine challenge the magnitude of DA release in the ventral striatum correlated inversely with anxiety ratings in healthy humans (Drevets et al, 2001). Moreover, the magnitude of dopamine release in the striatum has been shown to be modulated by 5-HT 2A receptor stimulation (Pehek et al, 2006;Porras et al, 2002;Yan, 2000), suggesting a mechanism through which the altered serotonergic function associated with tryptophan depletion may exert secondary effects on other neurotransmitter systems and thereby influence anxiety symptoms. Finally, the caudate responds preferentially to salient stimuli, whether or not such stimuli are associated with reward (Knutson et al, 2003;Schultz et al, 2003;Zink et al, 2006Zink et al, , 2004.…”
Section: Discussionmentioning
confidence: 99%
“…Hallucinogens may activate dopaminergic pathways either directly, as with LSD, or indirectly by compounds that lack significant dopamine receptor affinity (Bortolozzi et al 2005;Ichikawa and Meltzer 1995;Pehek et al 2006;Vollenweider et al 1999). For example, it is well documented that activation of the 5-HT 2A receptor can modulate dopamine levels or physiological responses mediated by dopaminergic systems (Alex and Pehek 2007;Lucas and Spampinato 2000;Pehek et al 2001;Vollenweider et al 1999;Yan 2000).…”
Section: Introductionmentioning
confidence: 99%